하위 경추 신연-굴곡 손상에 대한 전방 유합술 후 발생한 골절 및 양측 후관절 탈구 - 김종길(Jong-Kil Kim); 김진홍(Jin-Hong Kim); 김경태(Kyung-Tae Kim); 송경진(Kyung-Jin Song) (The journal of the Korean Orthopaedic Association, 2022)
단순 방사선 사진상 저명한 불안정성이 보이지 않으면서 신경증상이 동반된 신연-굴곡 손상에서 전방 금속판을 이용한 전방 유합술 후 후관절 완전 탈구로 진행되는 경우는 매우 드문 것으로 생각된다. 단순 방사선 사진상에서는 골절이나 전위가 발견되지 않아 자기공명영상 촬영과 컴퓨터 단층촬영으로 제6–7 경추, 제7 경추–제1 흉추 간 손상을 확인 후 케이지와 전방금속판을 이용한전방 유합술(C6–T1)을 시행하였다. 하지만 술 후 3일에 심한 경부통과 상지 방사통이 동반된 제6–7 경추 양측 후관절 탈구가 발생되어 후방 감압 및 후방고정술(C4–T1)을 시행한 경우가 있어 이를 보고하고자 한다. A bilateral facet dislocation after anterior cervical fusion with a plate in distraction-flexion injury without significant instability in plain radiography is very rare. This paper reports a case with a confirmed injury status (C6–7 and C7–T1) by magnetic resonance imaging and computed tomography with no visible fractures or displacement on plain radiography. Anterior cervical fusion (C6–T1) was performed with a cage and plate. On the other hand, three days later, C6–7 bilateral facet dislocation developed with severe neck and radiating pain, and posterior decompression and fusion were performed. KCI Citation Count: 0